Isolation and Antibacterial Activity assay of Endophytic Symbiont Bacteria on Seaweed Gracilaria verrucosa originated from Batu Meja Tongkaina Beach, North Sulawesi - Sirri, Yolanda; Warouw, Veibe; Rumengan, Inneke Fenny; Paransa, Darus Sa'adah; Undap, Suzanne Lydia; Ginting, Elvy Like (Jurnal Ilmiah Platax, 2022)
Seaweed can produce bioactive compounds such as antibacterial. Seaweed co-exists with bacteria endophytes. Entophytic bacteria are bacteria that live in host tissues and have the ability to protect the host itself by producing antibacterial compounds against pathogens. Therefore, the endophytic bacteria of seaweed symbionts can be utilized to produce antibacterial compounds. Bacteria can be mass-cultured because of their fast-growing characteristic. The aim of this study was to determine the antibacterial activity from endophytic symbiont bacteria on seaweed Gracilaria verrucosa originated from Batu Meja Tongkaina Beach, North Sulawesi. Isolation of bacteria was carried out by dilution steps from 101 to 10Ö¾3 times, then cultivation on Nutrient Agar media to obtain a single colony of the bacteria. Antibacterial activity was tested used paper disc diffusion method. The pathogens used were bacterial strains of Escherichia coli, Staphylococcus aureus, Streptococcus mutans, and Salmonella typhi. Moreover, antibiotics were used as positive controls. The antibacterial ability of the symbiotic bacteria was measured based on inhibition zones around the paper disc containing the isolates of endophytic bacteria. A total of 6 endophytic bacterial isolates were found, namely isolate B, C, D, E, F and G, characterized by different morphological features. The results showed that isolates B and C having inhibition zone of 0.5 â€“ 1.0 mm against S. typhi, indicating that these two isolates produce antibacterial compounds with a weak ability Â against S. typhi.